(untitled) (Damu Journal of Sport Sciences, 2025)
This study aimed to identify the societal challenges facing female students when joining school teams in Baghdad. This study relies on a descriptive analytical approach and a study population of female students participating in school sports teams. A stratified random sample of female players representing the education teams from Baghdad Education was selected. The researcher developed a scale and conducted scientific procedures for it, analyzing four main areas: cultural and social challenges, academic and organizational challenges, psychological and personal challenges, and logistical and material challenges. The results showed that all challenges were statistically significant, indicating their significant impact on female student participation. Psychological and personal challenges ranked first, followed by cultural and social challenges, academic and organizational challenges, and finally logistical and financial challenges. These findings point to the need for supportive strategies that include community awareness, improving sports infrastructure, and providing academic and psychological support for female students. The study recommends intensifying educational and sports efforts to enhance female students' participation in school teams.